The Application of the Scramble Method to Improve Indonesian Language Learning Outcomes of Third Grade Students at State Elementary School 002 Rambah - Ananda, Bunga Kasih; Adawiyah, Minni; Cahaya, Nur; Holijah, Nur; Sahdiah, Nur; Pasaribu, Satria Wijaya; Sahrawi, Sifa; Efendi, Rinja (Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to describe the application of the Scrumble method (a game of arranging letters/words) in an effort to improve the learning outcomes of Indonesian language in grade 3 students at SD 002 Rambah. Low interest in reading and mastery of vocabulary is the background for this research. The research method used is qualitative descriptive with a Class Action Research (PTK) design consisting of two cycles. The subject of the study was a 3rd grade student of SD 002 Rambah. Data collection techniques are carried out through participatory observation, in-depth interviews, and documentation of student work. Data analysis uses interactive analysis techniques that include data reduction, data presentation, and conclusion drawn. The results of the study show that the application of the Scrumble method is able to create an active and fun learning atmosphere. Qualitatively, there was a significant increase in students' ability to compose sentence structures, vocabulary enrichment, and courage in expressing ideas in writing. The improvement in learning outcomes can be seen from the completeness of the material understanding which is more evenly distributed than before the application of the method. It can be concluded that the Scrumble method is effective in improving the quality of the Indonesian language learning process and outcomes of elementary school students.